Is Partisan Alignment Electorally Rewarding? Evidence from Village Council Elections in India - Subhasish Dey; Kunal Sen (Institute for the Study of Labor (IZA), 2016)
Do ruling parties positively discriminate in favour of their own constituencies in allocating public resources? If they do, do they gain electorally in engaging in such a practice? This paper tests whether partisan alignment exists in the allocation of funds for India's largest social protection programme, the National Rural Employment Guarantee Scheme (NREGS) in the state of West Bengal in India, and whether incumbent local governments (village councils) gain electorally in the practice of partisan alignment. Using a quasi-experimental research design, we find that the village council level ruling-party spends significantly more in its own party constituencies as compared to opponent constituencies. We also find strong evidence of electoral rewards in the practice of partisan alignment. However, we find that the results differ between the two main ruling political parties at the village council level in the state.
Keywords: H53; I38; 330; National Rural Employment Guarantee Scheme; partisan alignment feedback effect; fuzzy regression discontinuity design